Socioeconomic factors affecting the job satisfaction levels of self-employed container truck drivers: a case study from Shanghai Port. Issue 5 (4th July 2017) - Jiang, Chenming; Lu, Linjun; Lu, Jian John
ABSTRACT: The job satisfaction level (JSL) of self-employed container truck drivers (SCTDs) is vital to the container trucking industry's (CTI) stability in China. An anonymous field survey of 645 SCTDs was conducted at Shanghai Port. Three ordered probit models were, respectively, developed to analyze the drivers' JSLs, their attitudes, and reactions to a CTI downturn. This study contributes to the literature that the demographic variables were not statistically significant for the SCTDs' current JSLs, while higher income SCTDs with fewer expenses were expected to have higher JSLs. During an industry downturn, drivers with families in Shanghai showed more job dissatisfaction. More working hours, lower income, expensive diesel fuel, a high consumer price index (CPI), and a low freight-to-distance ratio (FDR) significantly lowered the JSLs. An increase in the price of diesel fuel and the CPI, and a lower FDR exposed the industry to risk and instability. Additionally, credible evidence indicated that as the dissatisfaction levels of SCTDs rise in a downturn, SCTDs implement more practical measures that may negatively affect the industry's stability as well as society's. Based on these findings, managerial or policy implications were proposed to efficiently improve SCTDs' JSLs and CTI stability in Shanghai.